Crystallization of Interstitial Liquid and Latent Heat Buffering in Solidifying Gabbros: Skaergaard Intrusion, Greenland - Namur, Olivier; Humphreys, Madeleine C. S.; Holness, Marian B. (Journal of Petrology, 2014)
New compositional profiles across plagioclase grains from the Layered Series (LS), Marginal Border Series (MBS) and Upper Border Series (UBS) of the Skaergaard intrusion are used to understand the mechanisms of cumulate rock solidification and the fate of the interstitial liquid. The data show that plagioclase crystals display three types of compositional profile over the whole intrusion, as follows. (1) Grains with normal zoning, which dominate the MBS and UBS. These are interpreted as having formed at the top of a crystal mush and then buried in the cumulate pile. Crystallization of the interstitial melt resulted in liquid differentiation and produced normally zoned rims on plagioclase cores. (2) Unzoned crystals, which dominate the upper part of the LS, also crystallized at the top of the mush and were then buried in mush with a low interstitial liquid fraction or one experiencing convective movements that kept the liquid to a constant composition. (3) Crystals with a mantle of decreasing An content followed by a rim of constant composition. Grains showing this complex zoning mostly occur in the lower parts of the LS. Depending on the stratigraphic position within the intrusion, the composition of the rim can be An56, An51 or An40. In the main magma body, these compositions (An contents) correspond to those of plagioclase primocrysts (e.g. cores) at the appearance of cumulus clinopyroxene (An56), Fe–Ti oxides (An51) and apatite (An40). Compositional buffering of plagioclase rims is interpreted as being a consequence of enhanced release of latent heat of crystallization at the appearance of new interstitial phases in the crystal mush. When a new phase saturates, the latent heat contribution to the global enthalpy budget of the system becomes sufficiently high to keep the interstitial melt at its liquidus temperature for a period of time that could exceed thousands of years. Under these conditions, equilibrium, adcumulus growth together with diffusion and possibly advection of chemical components result in the formation of plagioclase rims of constant composition (An content). Efficient thermal buffering of the mush liquid depends on the porosity (i.e. fraction of liquid within the mush) and the degree of compositional homogeneity of the mush. In a heterogeneous and highly porous mush, saturation of the new phase occurs in the coldest part of the mush and the enhanced latent heat release at the saturation of this phase is quickly dissipated to the whole volume of liquid, including the warmest part that is not yet saturated in a new phase. As a consequence, no thermal buffering occurs and interstitial crystallization produces grains with normal zoning. The distribution of the various types of plagioclase grains throughout the Skaergaard intrusion can therefore be used to infer the spatial variability in the physical properties of the crystal mush, such as the residual porosity, both at an intrusion-wide scale and at a millimetre- to centimetre-scale.